Del favor debilis al favor consumatore: consideraciones históricas - Isler Soto, Erika (2019)
This paper refers to the historical evolution of the favor debilis principle from the Roman Law until our days. In this way, it begins with an examination of the favor libertatis principle and its incidence on the debtor’s responsibility, as well as the contractual interpretation in Ancient Rome. Subsequently, it refers to the incidence of Christianity in the moralization of the obligation. Then, the text refers to the persistence of the favor debilis under the modern model based on the conception of a free man that is able to protect its rights. Finally, its persistence in postmodernity is analyzed, which suggests changes in the law of obligations and contracts, which proposes also a new moralization of the contract, but sustained this time in the fundamental rights, as well as a renewed anthropocentric vision. Then, it refers to the bases of rules more favorable to the consumer and ends with the revision of the functions of the pro consumer principle: interpretation and conflict resolution mechanism of standards.